60+10X-K=0

Simple and best practice solution for 60+10X-K=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 60+10X-K=0 equation:


Simplifying
60 + 10X + -1K = 0

Reorder the terms:
60 + -1K + 10X = 0

Solving
60 + -1K + 10X = 0

Solving for variable 'K'.

Move all terms containing K to the left, all other terms to the right.

Add '-60' to each side of the equation.
60 + -1K + -60 + 10X = 0 + -60

Reorder the terms:
60 + -60 + -1K + 10X = 0 + -60

Combine like terms: 60 + -60 = 0
0 + -1K + 10X = 0 + -60
-1K + 10X = 0 + -60

Combine like terms: 0 + -60 = -60
-1K + 10X = -60

Add '-10X' to each side of the equation.
-1K + 10X + -10X = -60 + -10X

Combine like terms: 10X + -10X = 0
-1K + 0 = -60 + -10X
-1K = -60 + -10X

Divide each side by '-1'.
K = 60 + 10X

Simplifying
K = 60 + 10X

See similar equations:

| 0.09xX=100.56 | | -11x+134=519 | | 4x^2=4x^2+4x-15 | | 2=3x+38 | | 39.95+.12x=19.95+.28x | | (5x+30)=125 | | 32+1.8c=-80 | | 12x+15=36-8x | | 12+4(x-2)= | | x-15x=-120 | | 6m-11=12-2m | | A+B+C=2 | | 3x-12/3x^2-12 | | 4X(x+1)=4x^2+4x-15 | | -4x+5(2x-40)=-140 | | N/25=25 | | Z^6-(1+2i)z^3-7+i=0 | | -86+23x=114+27x | | 5(3+m)-4= | | 4x^2-16x+3y^2-24y+100=0 | | f(-x)=x^2+3x+7 | | 2x-18=4x-29+13 | | 5(2l+8)=90 | | 3/8x4/6= | | 6x^2=136+10x | | 7f=5f+18 | | 5(3)+5(m)-4= | | 2x-19=x-6+9+23 | | 0.09xX=71.93 | | 8/5=3x/15 | | 12=-4(-6-5) | | X^3+39x=16x^2 |

Equations solver categories